[83] Lateral suspension of cystocoele prolapse by laparoscopic robotic surgery: A series of 27 patients - Redouane Rabii (Taylor & Francis Group, 2018)
Objective: To evaluate the efficacy of lateral suspension of cystocoele prolapse by laparoscopic robotic surgery using a vaginal mesh. Genital prolapse is frequent and can be found in ∼50% of parous women. Its aetiology is complex and multifactorial. Developments in surgical techniques and synthetic material in the last 20 years have enabled us to use minimally invasive procedures with improved postoperative course and decreased recurrence rates. Methods: We report on 27 cases of women with cystocoeles. The treatment was a laparoscopic robotic surgery using a vaginal mesh with lateral suspension. From January 2016 to March 2017, 27 women with genital prolapse were included in a continuous series. The treatment was a laparoscopic robotic surgery using a vaginal mesh with lateral suspension. Data concerning patient characteristics (age, parity, menopause, body mass index, surgical history) were identified, as well as functional symptoms. Postoperative anatomical and functional status was evaluated by each operator on a regular basis. Results: The mean operative time was 102 min and the mean postoperative stay was 1.8 days. In the 27 procedures, there was a case of subtotal hysterectomy and in three cases urinary incontinence treatment. Bladder injury was noted in one patient. No case of conversion to laparotomy was encountered. Conclusion: Our experience in managing genital prolapse by robotic laparoscopy with the placement of lateral suspension prosthesis gives satisfactory results. We report a low rate of complications, and anatomical and functional results comparable to other techniques.